Eye movements reflect thought patterns while listening to literary narratives - Mézière, Diane; Kaakinen, Johanna K.; Lehtola, Jarkko; Kukkonen, Karin; Smallwood, Jonathan; Simola, Jaana (Elsevier BV, 2026)
While listening toan audiobook, listeners' attention may shift between the text and self-generated thoughts occurring during mind-wandering. Despite the growing use of audiobooks, little is known about how listeners process text when listening to it. The present study investigated the types of thought patterns that listeners have while listening to an audiobook, and whether and how these are reflected in eye movements. Participants (NStudy1 = 63, NStudy2 = 58) listened to an audio recording of a novel and responded to a 13-item mind-wandering questionnaire and a simple memory question 30 times during the listening task. In study 2, participants' eye movements were also recorded while they looked at a fixation cross on a screen. A principal components analysis (PCA) of the mind-wandering questionnaire responses produced four components in Study 1, and three components in Study 2. Three components were replicated across the two studies: Immersion, Mind-wandering, and Sub-vocalization. We then examined how these thought patterns were reflected in eye movementsin Study 2 including: fixation duration, fixation count, fixation dispersion, saccade amplitude, blink duration, and blink count. The results showed that higher levels of immersion was characterized by fewer and less dispersed fixations on the screen, shorter saccades, and longer blinks. Mind-wandering was related to more dispersed fixations. Sub-vocalization resulted in more fixations, higher dispersion across the screen, and more blinks. The results suggest that eye movements reflect shifts in attentional focus while listening to a literary text. The results provide important information about the processes underlying literary experience.